(untitled) (Research, Society and Development, 2021)
Objective: to assess the knowledge of intensive care nurses about the daily awakening of patients in critical care. Method: this is an experience report carried out by nurses residing in the Intensive Care program, in a public hospital in the city of São Paulo, in 2021. Results: it was noticed that the practice of daily awakening is in fact little used in the studied ICU and, when initiated, the attitude usually comes from the medical team, with little autonomy of nurses in these cases, also showing the lack of institutional protocol to support nurses’ actions in this area. Conclusion: corroborating the concept that there are educational needs that need to be met in the context of critical care in relation to health professionals, especially nurses, we conclude by proposing two suggestions for the highlighted environment, the first being the promotion of permanent education in health focused on continuous sedation and daily awakening of critical patients, and the second, the development and implementation of a care protocol in this aspect, aiming at an evidence-based and institutionally supported health practice.